2006
DOI: 10.1161/01.hyp.0000240331.32352.0c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Diabetic Nephropathy

Abstract: D iabetic nephropathy is a major microvascular complication of diabetes, representing the leading cause of endstage renal disease in the Western world, and a major cause of morbidity and mortality in both type 1 and type 2 diabetic subjects. Clinical hallmarks of diabetic nephropathy include a progressive increase in urinary albumin excretion and a decline in glomerular filtration rate (GFR), which occur in association with an increase in blood pressure, ultimately leading to endstage renal failure. 1 These re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
109
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 82 publications
1
109
0
9
Order By: Relevance
“…Evidence for microvascular damage is suggested by the correlation between increased Z c and urine albumin levels in our study. Increased glomerular perfusion pressure, as might be seen if pressure pulsatility increases, is known to lead to renal microvascular damage (30). Our data suggest that changes in the central aorta may precipitate renal microvascular change or, conversely, that early microvascular damage in the kidney may contribute to increases in pressure and flow pulsatility at all levels of the circulation.…”
mentioning
confidence: 50%
“…Evidence for microvascular damage is suggested by the correlation between increased Z c and urine albumin levels in our study. Increased glomerular perfusion pressure, as might be seen if pressure pulsatility increases, is known to lead to renal microvascular damage (30). Our data suggest that changes in the central aorta may precipitate renal microvascular change or, conversely, that early microvascular damage in the kidney may contribute to increases in pressure and flow pulsatility at all levels of the circulation.…”
mentioning
confidence: 50%
“…Hypertension is known to accelerate the progression of renal disease in patients with diabetes (29). In addition to the well-known association between narrow arteriolar calibers and coexisting hypertension (30)(31)(32), a meta-analysis and data pooling study showed that narrow retinal arteriolar calibers appear to precede clinical hypertension (33).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of hypertension on outcomes is exponential rather than linear. 9 Even in normotensive diabetic patients, lowering blood pressure can be beneficial in controlling diabetic nephropathy and retinopathy. 10 In particular, in patients with type 2 DM, the risk of diabetic nephropathy and retinopathy was independently and additively attributable to hypertension and hyperglycemia.…”
Section: Clinical and Epidemiological Evidence Of The Detrimental Effmentioning
confidence: 99%
“…10 In particular, in patients with type 2 DM, the risk of diabetic nephropathy and retinopathy was independently and additively attributable to hypertension and hyperglycemia. 6 Arterial hypertension is a main risk factor in the development and progression of diabetic nephropathy, 9 and a sustained reduction in blood pressure is probably the most effective single intervention to slow the progression of nephropathy in type 1 and type 2 DM. 7,[9][10][11] In the Wisconsin Epidemiology Study of DR, the presence of hypertension in type 1 diabetic patients was associated with a 73% increase in the risk of incident proliferative DR. 12 More recently, the Wisconsin Epidemiology Study of DR demonstrated that the 25-year incidence of visual impairment was related to poorer glycemia control and the presence of arterial hypertension.…”
Section: Clinical and Epidemiological Evidence Of The Detrimental Effmentioning
confidence: 99%